Dampak Pemasaran Word of Mouth Dan Mutu Produk Terhadap Keputusan Pembelian Serta Kepuasan Pelanggan Sebagai Variabel Intervening Pada Rumah Makan Sate Tegar Kunduran, Blora - Muhamad Bagas Handoko; Indriasari , Ika; indiworo , Hawik Ervina (Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang, 2025)
The culinary business is a business that is widely carried out by some people because it is easier and faster to be recognized, and to instill a good impression on consumers faster. The type of research used in this study is quantitative research. The analysis method used is the multiple regression analysis method. The population in this study were consumers of Sate Tegar Restaurant. The sample of this study was 200 consumers. This study in sampling using probability sampling. The sampling technique used was Slovin. The results of this study are word of mouth affects customer satisfaction, product quality does not affect customer satisfaction, customer satisfaction affects purchasing decisions, word of mouth affects purchasing decisions, product quality does not affect purchasing decisions, word of mouth on purchasing decisions through customer satisfaction does not have a significant effect, product quality on purchasing decisions through customer satisfaction don’t have a significant effect.Keywords: Word of Mouth, Price, Product Quality, Customer Satisfaction, Purchasing Decisions.